Communicative action and journalism in difficult times - Paredes Ramírez, Willington (Scripta Mundi, 2024)
The purpose of this essay is to determine the communicative action of Ecuadorian investigative journalism, framed in a series of sociocultural and ideological events carried out by certain and concrete social actors, and in which they directly influence and influence different social sectors. In the historical context, a set of economic, social, political and ideological interests, individual and collective, are identified, which directly and indirectly influence the work of the journalist, committed to a free, analytical, critical and relatively independent communicative action, who seeks, by all means, to exercise his profession without these obstacles and blockages. A brief historical synopsis is presented of the most notorious cases of corruption, which the diligence of journalism and the investigative press brought to light in Ecuador between 1960 and 2020. Among the main conclusions, it can be established that investigative journalism, as a communicative action, which becomes a real and effective task in the work of journalists, is nothing other than a form of action. A specialized method, with a lot of responsibility and civic, ethical, and also ideological-political commitment, of “audacity and daring” of those who seek the truth for society. That is why in the communicative action of journalism, especially when it is critical, analytical and objective, there will always be risks.